Relationship and Elasticity of Indonesia’s Tobacco Cigars with Major Competitors in the International Market - Yafi, Muhammad Ali; Suharno, Suharno; Erwidodo, Erwidodo (Agro Bali : Agricultural Journal, 2024)
Indonesia's tobacco has good potential for exporting to the world market. Cigars are one of the derivative products that can compete with other exporting countries in the world. The trend of Indonesian cigar exports in 2022 has decreased. The study aims to identify the relationship between Indonesian cigars and competing countries in the international market. The research data to be observed uses HS code 240210 by comparing competitor countries between Indonesia, the Dominican Republic, Belgium, Netherlands, Germany, Spain, and Hungary. The analysis method used is the AIDS (Almost Ideal Demand System) model, which will describe the price elasticity of demand, cross-price, and income. The results obtained are based on the income elasticity of Indonesian cigars, including normal goods, with a value of 0.0287. The cross-price elasticity results show that Indonesian cigars tend to compete with Netherlands, Belgium, Spain, and Hungary cigars because they are positive. Meanwhile, Indonesian cigars are related to the Dominican Republic and Germany as complementary goods. Based on the results of the price elasticity of demand, a negative value is obtained, including Indonesian cigars, which means that the demand for Indonesian cigars is inelastic.